PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Yuniep Mujati Suaidah; Langgeng Prayitno Utomo (Ekonis: Jurnal Ekonomi dan Bisnis, 2018)
This research aims to examine influence of good corporate governance mechanisms on earnings management in manufacturing companies. Good Corporate Governance mechanisms in this research measured by audit committee, independent commissioner, managerial ownership and profitability. This research is descriptive quantitative research. Sampling was purposive sampling method, in order yo obtain a sample of 11 manufacturing companies listed in The Indonesian Stock Exchange in 2014 until 2016. Method of analysis in this research is regression analysis after done classic assumption test. The result shows that partial examination, audit committee and board of independent commissioner did not significant influence to earnings management. Managerial ownership and profitability has a significant influence to earnings management. While the simultaneously influence of good corporate governance machanisms consist of audit committee, board of independent commissioner, managerial ownership and profitability has significant influence to earnings management. Keywords: Good Corporate Governance Mechanisms, Audit Committee, Independent Commissioner, Managerial Ownership, Profitability, and Earnings Management.